2011
DOI: 10.1017/s0143385711000174
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of moments for Axiom A and non-uniformly hyperbolic flows

Abstract: In the paper, we prove convergence of moments of all orders for Axiom A diffeomorphisms and flows. The same results hold for nonuniformly hyperbolic diffeomorphisms and flows modelled by Young towers with superpolynomial tails. For polynomial tails, we prove convergence of moments up to a certain order, and give examples where moments diverge when this order is exceeded.Nonuniformly hyperbolic systems covered by our result include Hénon-like attractors, Lorenz attractors, semidispersing billiards, finite horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…The situation for uniformly expanding/hyperbolic (Axiom A) systems is easily described: all moments |S n f | p dµ grow like n p/2 and moreover |n −1/2 S n f | p dµ converges to the p'th moment of the limiting Gaussian in the central limit theorem. [MT12b] showed that convergence of all moments holds also for nonuniformly expanding/hyperbolic diffeomorphisms modelled by Young towers with exponential tails [You98]. However, it follows from [MN08,MT12b] that the situation is quite different for systems modelled by Young towers with polynomial tails [You99].…”
Section: Statement Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation for uniformly expanding/hyperbolic (Axiom A) systems is easily described: all moments |S n f | p dµ grow like n p/2 and moreover |n −1/2 S n f | p dµ converges to the p'th moment of the limiting Gaussian in the central limit theorem. [MT12b] showed that convergence of all moments holds also for nonuniformly expanding/hyperbolic diffeomorphisms modelled by Young towers with exponential tails [You98]. However, it follows from [MN08,MT12b] that the situation is quite different for systems modelled by Young towers with polynomial tails [You99].…”
Section: Statement Of Resultsmentioning
confidence: 99%
“…[MT12b] showed that convergence of all moments holds also for nonuniformly expanding/hyperbolic diffeomorphisms modelled by Young towers with exponential tails [You98]. However, it follows from [MN08,MT12b] that the situation is quite different for systems modelled by Young towers with polynomial tails [You99].…”
Section: Statement Of Resultsmentioning
confidence: 99%
“…A consequence is deterministic homogenisation (convergence to a stochastic differential equation) for fast-slow dynamical systems whenever the fast dynamics is singularly hyperbolic of codimension two. such as expansivity [9], the central limit theorem (CLT) [17], moment estimates [28], and exponential decay of correlations [6].Recently, [31] (see also previous work of [14]) gave an analytic proof of existence of geometric Lorenz attractors in the extended Lorenz modelA consequence of the current paper, in conjunction with [8], is that CLTs and moment estimates hold for these attractors. Exponential decay of correlations remains an open question: the proof in [6] relies on the existence of a smooth stable foliation for the flow, which holds for the classical Lorenz attractor [7] but not for the examples of [14,31].…”
mentioning
confidence: 83%
“…A consequence is deterministic homogenisation (convergence to a stochastic differential equation) for fast-slow dynamical systems whenever the fast dynamics is singularly hyperbolic of codimension two. such as expansivity [9], the central limit theorem (CLT) [17], moment estimates [28], and exponential decay of correlations [6].…”
mentioning
confidence: 99%
“…By the triangle inequality, it follows from (3.4) and (3.5) that The bound on moments in Proposition 3.8 together with the distributional limit law in Proposition 3.7 implies convergence of lower moments, (see for example[21]), and so lim n→∞ n X×S 1 ) = S Y (ω)/r. Now n−1 j=0 u(f j ω (x, ϕ)) = e iϕ n−1 j=0 e ijω v(f j (x)) and so | n−1j=0 u • f j ω | L 2 (X×S 1 ) = | n−1 j=0 e ijω v • f j | L 2 (X) .…”
mentioning
confidence: 96%